Analsis Tingkat Pengetahuan Akseptor KB Tentang Alat Kontrasepsi di Puskesmas Sedayu I Tahun 2014 - Sundari Mulyaningsih; Susiana Sariyati (Alma Ata University Press, 2014)
Family planning is an effort to support the national policy of family planning program. One of indicators family planning programs is existing acceptors and Contraceptive Prevalence Rate (CPR). CPR is the percentage of devides used by fertile couple. The purpose of this research is to identify acceptors’ level of knowledge contraceptive devices at Puskesmas Sedayu I. This observational research used cross sectional approach. A method of the research is survey. The population in this research is acceptors of family planning in Yogyakarta. The sample in this research is 33 family planning acceptors in Yogyakarta. This research found that understanding acceptors about contraceptive devices are low (54,5%), acceptors aged between 21-35 years was the majority (24 respondents or 72,7%), understanding of description family planning devices was in average level at about (69,7%), understanding the type of contraception devices was average (36,4%), understanding of example the contracentive devices was great (63,6%), and understanding of beneﬁ t the contraceptive devices was low (48,5%).